Strategi komunikasi pemasaran Dinas Kepemudaan Olahragara dan Pariwisata (DISPORAPAR) dalam mempromosikan wisata budaya festival perang di Kabupaten Kepulauan Meranti pasca covid 19 - Aminuddin, Imam; Rumyeni, Rumyeni; Yozani, Ringgo Eldapi (Jurnal Teknik Industri Terintegrasi (JUTIN), 2025)
This research aims to analyze the marketing communication strategy carried out by the Meranti Islands Regency Youth Sports and Tourism Service (DISPORAPAR) in promoting the Water War Festival (Cian Cui) after the COVID-19 pandemic. The research method used is a qualitative descriptive approach with data collection techniques through interviews, observation and documentation. Informants were selected using purposive sampling involving festival managers, participants and visitors. The research results show that DISPORAPAR's marketing communication strategy uses the promotional mix concept within the Integrated Marketing Communication (IMC) framework. Although not all elements of IMC are implemented, strategies that include advertising through print media, promotions through banners, social media, mass media, public relations activities, and organizing events have been proven to increase the number of tourist visits. The main challenges faced are budget and infrastructure limitations. This research recommends improving infrastructure and optimizing digital marketing strategies to introduce the festival to a wider audience